2020
DOI: 10.1021/jacs.0c04091
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis and Antimicrobial Evaluation of the Guanidinium Alkaloid Batzelladine D: Development of a Stereodivergent Strategy

Abstract: Herein, we describe a stereodivergent route to (±)-batzelladine D (2), (+)-batzelladine D (2), (−)-batzelladine D (2), and a series of stereochemical analogues and explore their antimicrobial activity for the first time. The concise synthetic approach enables access to the natural products in a sequence of 8–12 steps from readily available building blocks. Highlights of the synthetic strategy include gram-scale preparation of a late stage intermediate, pinpoint stereocontrol around the tricyclic skeleton, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Those interesting findings figured out that such distinct molecular architectures are merited and could enlighten the development of promising antiviral leads for paving the COVID-19 pandemic. Moreover, considering the feasible total chemical syntheses for a notable number of these compounds [ 31 , 41 , [82] , [83] , [84] ] or structurally related congeners could be encouraging for more in vitro / in vivo preclinical investigations for COVID-19 control.…”
Section: Discussionmentioning
confidence: 99%
“…Those interesting findings figured out that such distinct molecular architectures are merited and could enlighten the development of promising antiviral leads for paving the COVID-19 pandemic. Moreover, considering the feasible total chemical syntheses for a notable number of these compounds [ 31 , 41 , [82] , [83] , [84] ] or structurally related congeners could be encouraging for more in vitro / in vivo preclinical investigations for COVID-19 control.…”
Section: Discussionmentioning
confidence: 99%
“…Those interesting findings figured out that such distinct molecular architectures are merited and could enlighten the development of promising antiviral leads for paving the COVID-19 pandemic. Moreover, considering the feasible total chemical syntheses for a notable number of these compounds [27,37,[62][63][64] or structurally related congeners could be encouraging for more in vitro /in vivo preclinical investigations for COVID-19 control.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, we found that an aza-Michael approach could be utilized to successfully prepare the target heterocycle. 4 To this end, our synthesis began with commercially available β-lactam 123, which was substituted with butenyl Grignard reagent 124, N-protected with TBS, and subsequently acylated to provide 127 in good yield over three steps (Scheme 1A). The reduction of the methyl ketone was required at this stage, and we have developed conditions to access both diastereomers (128 and 129) in good yields, ultimately enabling access to both the natural product 4 and its epimer 141 via subsequent displacement (Scheme 1A).…”
Section: ■ Lipoxazolidinone Natural Productsmentioning
confidence: 99%
“…We explored a number of approaches to form the bicyclic scaffold either directly or from a monocyclic β-lactam building block but were met with challenges due to the increased strain of the fused four- or five-ring system and the appended side chains at their necessary oxidation states. Fortunately, we found that an aza-Michael approach could be utilized to successfully prepare the target heterocycle . To this end, our synthesis began with commercially available β-lactam 123 , which was substituted with butenyl Grignard reagent 124 , N-protected with TBS, and subsequently acylated to provide 127 in good yield over three steps (Scheme A).…”
Section: Batzelladine Natural Productsmentioning
confidence: 99%